2006
DOI: 10.4141/p05-148
|View full text |Cite
|
Sign up to set email alerts
|

A review of copper fertilizer management for optimum yield and quality of crops in the Canadian Prairie provinces

Abstract: . A review of copper fertilizer management for optimum yield and quality of crops in the Canadian Prairie Provinces. Can. J. Plant Sci. 86: 605-619. Deficiency of copper (Cu) in Canadian prairie soils is not widespread, but whenever it occurs it can cause a drastic reduction in seed yield and quality of most cereals, especially wheat. Field experiments conducted in western Canada indicated that broadcast-incorporation of granular Cu fertilizers prior to seeding at 3-5.6 kg Cu ha -1 was usually sufficient to pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 32 publications
1
11
0
Order By: Relevance
“…A similar but less pronounced effect was obtained by P and Zn fertilizers on durum wheat. The results agree with numerous research reports summarized by Malhi and Karamanos (2006).…”
Section: Fe Mn and Cusupporting
confidence: 93%
“…A similar but less pronounced effect was obtained by P and Zn fertilizers on durum wheat. The results agree with numerous research reports summarized by Malhi and Karamanos (2006).…”
Section: Fe Mn and Cusupporting
confidence: 93%
“…This soil did have a very low supply rate (< 0.05 µg Cu 10 cm −2 24 h −1 ) of available Cu according to assessment with resin membrane probe that may reflect limited mobility by diffusion in this high clay content soil. Various studies have shown the beneficial effect of Cu fertilization for optimizing wheat yields on Cu deficient mineral soils of Canadian prairies 12 , 31 34 . Previously, it was reported that soils containing DTPA-extractable Cu levels of less than 0.40 mg kg −1 are critically deficient, in which economic yield response to Cu fertilization is expected 12 .…”
Section: Resultsmentioning
confidence: 99%
“…Critical whole plant Cu concentration of less than 2 mg kg −1 50 , 2.5 to 3.0 mg kg −1 51 and 5 mg kg −1 49 , 52 are reported as indicators of potential deficiency in wheat. However, the whole plant Cu concentration is often weakly correlated to grain and straw biomass yield responses to fertilization 34 , 50 . Copper fertilization of wheat with a tissue concentration of greater than 2 mg Cu kg −1 at mid-late tillering stages may not be effective for yield improvement 53 .…”
Section: Tissue Concentrationmentioning
confidence: 99%
“…As with Co, soil and herbage levels are also poor indicators of Cu deficiency (Fisher, 2008). However, the large number of samples analysed for Cu possibly reflects its importance not only for animal health but also for crop yield and quality (Malhi & Karamanos, 2006). Although only a small number of samples were analysed for Mo, 60% of these had VL or L status.…”
Section: Discussionmentioning
confidence: 99%